2020
DOI: 10.1038/s41598-020-72216-y
|View full text |Cite
|
Sign up to set email alerts
|

Adeno-associated virus-mediated gene delivery promotes S-phase entry-independent precise targeted integration in cardiomyocytes

Abstract: Post-mitotic cardiomyocytes have been considered to be non-permissive to precise targeted integration including homology-directed repair (HDR) after CRISPR/Cas9 genome editing. Here, we demonstrate that direct delivery of large amounts of transgene encoding guide RNA (gRNA) and repair template DNA via intra-ventricular injection of adeno-associated virus (AAV) promotes precise targeted genome replacement in adult murine cardiomyocytes expressing Cas9. Neither systemic injection of AAV nor direct injection of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 40 publications
2
18
0
Order By: Relevance
“…It should be noted most of in vivo hepatocytes are in G0, which is considerably different from cultured cells and could contribute to the discordance 46 . Recently, it was reported that AAV-HR in cardiomyocytes occurred independently of S phase entry, which is in line with our present data 47 . This lack of S phase progression in HR+ hepatocytes prompted the hypothesis that udarabine may have effects on non-proliferating hepatocytes.…”
Section: Discussionsupporting
confidence: 94%
“…It should be noted most of in vivo hepatocytes are in G0, which is considerably different from cultured cells and could contribute to the discordance 46 . Recently, it was reported that AAV-HR in cardiomyocytes occurred independently of S phase entry, which is in line with our present data 47 . This lack of S phase progression in HR+ hepatocytes prompted the hypothesis that udarabine may have effects on non-proliferating hepatocytes.…”
Section: Discussionsupporting
confidence: 94%
“…Gene-specific strategy Limited to gene body mutations Urnov et al, 2005;Lombardo et al, 2007;Li et al, 2011;Genovese et al, 2014;Voit et al, 2014;Dever et al, 2016;Hubbard et al, 2016;Schiroli et al, 2017;Sweeney et al, 2017;Kuo et al, 2018;Wang et al, 2019Wang et al, , 2020aRai et al, 2020 (Hubbard et al, 2016;Kuo et al, 2018), and Wiskott-Aldrich Syndrome (Rai et al, 2020). Beside HSC and terminally differentiated blood cells, like B and T cells (Wang et al, 2016;Hung et al, 2018), AAV and nucleases have been the preferred method to achieve targeted transgene integration in many tissues in vivo (Suzuki et al, 2019;Kohama et al, 2020;Nishiguchi et al, 2020), especially the liver.…”
Section: A Endogenous Locus Physiological Transgene Expression Corrects Multiple Mutationsmentioning
confidence: 99%
“…Viral delivery systems such as vectors based on adeno-associated virus (AAV), adenovirus, or lentivirus are able to transduce non-dividing cells [ 84 ]. For cardiomyocytes, AAV vector delivery enables HDR in murine adult heart tissues and human cardiomyocytes differentiated from induced pluripotent stem cells (hiPSCs) independently of the cell cycle stage [ 73 ]. In contrast to AAV, for adenovirus (AdV) vectors, genomic integration is rather an exception.…”
Section: The General Approach Of Gene Editingmentioning
confidence: 99%
“…In contrast to AAV, for adenovirus (AdV) vectors, genomic integration is rather an exception. In cultured neonate cardiomyocytes, however, some limited integration was observed for cells which had entered S-phase [ 73 ]. Viral vector systems vary in their packaging capacity, the genetic material (DNA/RNA), and the vector genome form.…”
Section: The General Approach Of Gene Editingmentioning
confidence: 99%